Antifungal photodynamic efficacy of Benzo[a]phenoxazinium chlorides against Candida albicans biofilms - Lopes, Marisa da Conceição Gomes (2013)
The use of photodynamic therapy (PDT) as a new approach to treat localized Candida infections is an emerging and promising field. The aim of this study was to verify the photodynamic efficacy against Candida albicans biofilms of two new benzo[a]phenoxazinium photosensitizers, N-[5-(3-hydroxypropylamino)-10-methyl-9H-benzo[a]phenoxazin-9-ylidene]ethanaminium chloride (FSc) and N-(5-(11-hydroxyundecylamino)-10-methyl-9H-benzo[a]phenoxazin-9-ylidene)ethanaminium chloride (FSd).